The Development of a Module Based on the Sas Method to Improve Reading and Writing Skills in Class II SDN 054905 Paya Redas - Wati, Lina; Fadillah, Nurul; Wulandari, Rika (Journal of General Education Science, 2023)
This research method uses the research and development method. This research aims to develop student learning modules that are suitable for student learning in lower grades, and improve the quality of teacher teaching in learning. The research was carried out at SDN 054905 Paya Redas with research subject II. The results of the research that has been carried out show that there are several students who have difficulty reading, there are still students who cannot distinguish letters and have not memorized the letters of the alphabet. One method that can motivate students to improve their learning is by using the SAS ( Synthetic Structural Analytical ) Method. Data collection techniques use documentation and questionnaires, while data analysis techniques use percentages . The result of the development stage is to produce a reading module product. Thus, it can be concluded that the development of reading skills modules is based on Synthetic Structural Analytical (SAS) is included in the very valid or very feasible category. Thus, it can be concluded that the feasibility of the beginning reading and writing module based on Synthetic Analytical Structural (SAS) in class II elementary school learning is included in the very feasible category.